PENGARUH KADAR Aspergillus niger TERHADAP PRODUKSI BIOETANOL DARI BONGGOL PISANG KEPOK ( Musa paradisiaca L) - Junaini Junaini; Elvinawati Elvinawati; Sumpono Sumpono (ALOTROP, 2019)
This study aims to determine the effect of Aspergillus niger levels on bioethanol production in banana cobs using Saccharfication Simultation Fermentation (SSF) method. This research uses banana kepok (Musa paradisiaca L.) obtained from Enggano Island of Bengkulu Province. Enggano Island is one of the outermost islands of Bengkulu Province which has a coordinate point of 5023'25,000 '' LS - 102014'16,000 '' BT. Samples of banana done preparation before the hydrolysis and fermentation process by smoothing the banana cobs using a blender until it becomes mush. Samples in the form of slurry were then added by Aspergillus niger and Sccharomyces cerevisiae. Hydrolysis performed for 72 hours which then continued with the fermentation process for 5 days. In the study there were 5 treatments: addition of Aspergillus niger 107 CFU/mL, addition of 10 mL Saccharomyces cerevisiae, addition of 10 mL Saccharomyces cerevisiae + Aspergillus niger 106 CFU/mL, 10 mL Saccharomyces cerevisiae + Aspergillus niger 107CFU/mL and 10 mL Saccharomyces cerevisiae + Aspergillus niger 108CFU/mL. The fermentation results were distilled and then measured the ethanol content by the specific gravity method. Ethanol content obtained from each treatment were 3.995%, 6.218%, 6.825%, 9.065%, and 12.348%, respectively. From one-way analysis test can be obtained the value of Fcount and Ftabel respectively are 25.73 and 5.19, so the value of Ftable< Fcount which means each treatment has a different result significantly.